Knowledge Exploitation, Inventor Characteristics, and Green Innovation Performance in Automotive Firms - Yu-Tong Liu; Seung-Yoon Rhee; Eun-Jung Hyun (Systems)
Optimizing knowledge exploitation strategies is a crucial challenge in promoting sustainable technology development. This study investigates how innovation characteristics, inventor attributes, and network structures influence the effectiveness of these strategies in firms’ green transition efforts. Our study focuses on the automotive industry—a sector characterized by long development cycles, high capital intensity, and strong path dependencies—as it undergoes a significant transition towards sustainable technologies. Using patent data from the Korean automotive industry, we uncover nuanced dynamics in the refinement and enhancement of green knowledge. While knowledge exploitation generally boosts innovative performance, this effect is significantly stronger for green innovations. Interestingly, high levels of inventor experience in green technologies weaken the positive impact of exploitation—a finding that challenges conventional expectations. Network structure also plays a pivotal yet often overlooked role: high network cohesion reduces the benefits of exploitation, while a broad network range enhances them. By shedding light on the hidden contributions of individual inventors and their networks, we deepen our understanding of the micro-foundations of green innovation within sustainability transitions. Our findings offer valuable insights for managers seeking to enhance their green knowledge strategies in industries undergoing technological shifts toward sustainability. We highlight previously underappreciated conditions under which exploitation strategies are most effective and factors that can be leveraged to elevate sustainable innovation performance through strategic knowledge enhancement.